Enhancing the Electromechanical Coupling in Soft Energy Harvesters by Using Graded Dielectric Elastomers - Lingling Chen; Shengyou Yang (Micromachines, 2021)
Soft dielectric elastomers can quickly achieve large deformations when they are subjected to electromechanical loads. They are widely used to fabricate a number of soft functional devices. However, the functions of soft devices are limited to the failure modes of soft dielectric elastomers. In this paper, we use graded dielectric elastomers to produce a soft energy harvester with a strong ability of energy harvesting. Compared to the conventional energy harvester with homogeneous dielectric films, our new energy harvester is made of graded elastomers and can increase both the specific energy from 2.70 J/g to 2.93 J/g and the maximum energy from 6.3 J/g to 8.6 J/g by just using a stiffer outer radius. By optimizing the material parameters in graded dielectric films, the soft energy harvester can reach better performance, and our results can provide guidance for designing powerful energy harvesters.